Ethics constructed through the process of nurse training: conceptions, spaces and strategies La ética que se construye en el proceso de formación de enfermeros: concepciones, espacios y estrategias A ética que se constrói no processo de formação de enfermeiros: concepções, espaços e estratégias - Flávia Regina de Souza Ramos; Laura Cavalcanti de Farias Brehmer; Mara Ambrosina de Oliveira Vargas; Dulcinéia Ghizoni Schneider; Laila Crespo Drago (Universidade de São Paulo, 2013)
OBJECTIVE: to discuss the professors' conceptions about the ethical dimension of nurse training based on the relationships which this establishes with the competencies with the professional profile; and to identify the spaces and strategies for the teaching of ethics in this process. METHOD: A qualitative study delineated as a case study. The data was collected based on focus groups with professors from six undergraduate nursing courses in the state of Santa Catarina, Brazil, totaling 50 subjects. Based on the professors' discourse, the conceptions and mutual relations between professional competencies, the formative process and ethics were analyzed. RESULTS: The results were organized and the discussion explored through the thematic categories: The ethics constructed in the process of training nurses - the professors' conceptions, and spaces and strategies for the teaching of ethics in nurse training. CONCLUSIONS: The issue of ethics was shown to be transversal in the formative process. The study evidenced the challenge of creating spaces and strategies for teaching and fosters discussion about the new demands for changes placed upon the nursing schools, about the suitability of the care setting, and about the exercising of critical and problem-based education. OBJETIVO: Discutir las concepciones de los profesores sobre la dimensión ética de la formación del enfermero, a partir de las relaciones que establece con las competencias del perfil profesional; e identificar los espacios y estrategias para la enseñanza de la ética. MÉTODOS: Estudio cualitativo delineado como estudio de caso. Los datos fueron obtenidos a partir de grupos focales, con profesores de seis cursos de pregrado en Enfermería del estado de Santa Catarina, totalizando 50 sujetos. RESULTADOS: Los resultados fueran organizados y exploran la discusión de dos categorías temáticas: La ética que construye en el proceso de formación en enfermería - las concepciones de profesores y Los espacios y estrategias para la enseñanza de la ética en la formación de enfermería. CONCLUSIONES: La ética se mostró transversal en el proceso formativo. El estudio mostró el reto de desarrollar espacios y estrategias de enseñanza y sus contribuciones fueron la discusión sobre las nuevas demandas por cambios presentadas a las escuelas y sobre la cualificación del escenario del cuidado y del ejercicio de la educación problematizadora y crítica. OBJETIVO: discutir as concepções de professores sobre a dimensão ética da formação do enfermeiro, com base nas relações estabelecidas entre ética, competências e perfil profissional, bem como identificar os espaços e estratégias para o ensino da ética nesse processo de formação. MÉTODO: estudo qualitativo, delineado como estudo de caso. Os dados foram coletados entre grupos focais, com professores de seis cursos de graduação de enfermagem de uma universidade do Estado de Santa Catariana, totalizando 50 sujeitos. Tomando-se como base o discurso dos professores, foram analisadas as concepções e mútuas relações entre competências profissionais, processo formativo e ética. RESULTADOS: os resultados foram organizados e exploram a discussão acerca das categorias temáticas: a ética que se constrói no processo de formação de enfermeiros, as concepções de professores e espaços e estratégias para o ensino da ética na formação em enfermagem. CONCLUSÕES: o tema da ética mostrou-se transversal no processo formativo. O estudo evidenciou o desafio de se criar espaços e estratégias de ensino e fomenta a discussão acerca das novas demandas por mudanças colocadas às escolas, da qualificação do cenário do cuidado e do exercício da educação problematizadora e crítica.